Micarea soralifera sp. nov., a new sorediate species in the M. prasina group. (3rd May 2016) - GUZOW-KRZEMIŃSKA, Beata; CZARNOTA, Paweł; ŁUBEK, Anna; KUKWA, Martin
Abstract: Micarea soralifera sp. nov., a new sorediate species belonging to the M. prasina group, is characterized by soralia developing directly from the endoxylic thallus or small external areoles, as well as the presence of micareic acid. Phylogenetic analyses of mtSSU rDNA sequences have shown that its closest relative is M. subviridescens . ITS rDNA sequence, a marker proposed as the universal barcoding region of fungi, was generated from the holotype.